V. P. Danevsky as a historian of international law - Havrylenko, O. A. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2016)
On the basis of analysis of a wide range of sources and literature, to explore the process of formation and development as a scientist – researcher of history of international law Kharkiv University Professor V. Danevsky (1852- 1898). The conclusion is that it belongs to a generation of lawyers, developments which have created the foundations of modern domestic legal science. His work, which in Soviet times for the ideological reasons have been forgotten and only briefly mentioned by researchers, contain many layers of information and scientific conclusions. This makes it possible not only to rank V. Danevsky among the most famous in his time in Europe experts in the field of international criminal law, but also to highlight its achievements in creating a foundation for further research in the field of history of international law.